Effect of Urea on Drug Extraction Efficiency in Reverse Iontophoresis - Rie Yamauchi; Shuji Ohno; Yasuko Obata (Pharmaceutics)
Background/Objectives: Reverse iontophoresis (R-IP) is a technology that transdermally delivers components from inside the body to outside the body using electroosmotic flow (EOF) generated by applying a low electric current through the skin. It has attracted attention as a non-invasive sampling method for therapeutic drug monitoring (TDM). The purpose of this study was to determine whether urea and Tween 80 effectively enhance drug extraction from beneath the skin using R-IP. Methods: An in vitro drug extraction test using hairless mouse skin and R-IP was performed with a 3-chamber Franz cell and Ag|AgCl electrodes by applying a constant current (0.25 mA/cm2) for 6 h. Acetaminophen was chosen as the model drug, and its solution (30, 100, or 300 μg/mL) was placed in the subdermal compartment. The pH of both the electrode and subdermal compartment solutions was maintained at 7.4. Results: Acetaminophen was gradually extracted into the electrode compartment in a concentration-dependent manner and was more abundant in the cathode compartment than in the anode compartment. In addition, urea significantly promoted drug extraction, particularly on the cathode side, and a linear relationship was observed between the subdermal concentration and extracted amount. This effect is likely due to skin hydration caused by urea, which enhances EOF generation in the skin. Conversely, Tween 80 had no effect on drug extraction. Conclusions: R-IP combined with urea is expected to not only shorten the treatment time but also enable its application to drugs with low concentrations in blood.